Experiences of operational managers regarding record keeping by new professional nurses in public hospitals in the North West province, South Africa - Naomi L. Nkoane (AOSIS, 2023)
Background: Documentation can be written or computerised and is used to communicate healthcare and treatment among healthcare professionals. Documentation is the tool that records and measures the healthcare provided to patients, and it must be accurate, complete and timely. Aim: This study aims to explore and describe the experiences of the operational managers regarding record keeping by new nurses in selected public hospitals in South Africa. Setting: The study was conducted in selected public hospitals in the North West province. Method: This study used a qualitative, explorative and descriptive approach with a purposive sampling method. A total of 35 operational managers participated in the process of data collection. Results: The following themes emerged from this study: gaps in record keeping, the impact of inaccurate documentation and the need for improvement in record keeping. Conclusion: The study has shown the need to bring technological innovation to strengthen the effective improvement of digitalisation in nursing record keeping in the facilities furthermore, nurses should be supported through programmes on intentional and mindful record keeping curbing the incidences of inaccuracy and incompleteness. Contribution: This study's findings confirmed that new nurses were not consistent with accurate documentation of patient records, and this needs further strengthening in public hospitals to have an impact on the health and safety of the patient.